The fate of the German population in former and new territories after the end of World War II (based on the example of Pomerania). Similarities and differences - Sudziński, Ryszard (Balcanica Posnaniensia. Acta et studia, 2001)
The article is devoted to an analysis of the situation of the German population living in the Vistula Pomerania region after the end of the Second World War. The author addresses the differing experiences of Germans living both in the territories of pre-war Poland and in the regions incorporated into the Polish state after 1945. He highlights similarities and differences in migration, expulsion, and social processes. The aim of the study is to present the principal directions of change affecting the German population in the Pomeranian region. The research employs a historical method based on archival materials, administrative documentation, Polish and German sources, and scholarly literature. The author notes that research on this subject was for many years hindered by limited access to archival sources held in Polish and Soviet archives. The article discusses the major processes shaping the fate of Germans after the war, including evacuation, spontaneous flight, deportations to the USSR, internment in labor camps, expulsions, and measures related to the rehabilitation of Volksdeutsche and the nationality verification of the indigenous population. The author emphasizes that the scale and character of these phenomena varied according to local social and administrative conditions. The conclusions indicate that the post-war experiences of Germans in Pomerania resulted from overlapping political, migratory, and social processes and that a comprehensive understanding of the issue became possible only after the opening of new archival collections after 1989.